Cost-Benefit Analysis of Drinking Water Fluoridation in 12-year-old Children in the Biobío Region, Chile. - Camilo Ulloa; Catherine de la Puente; Fernando Rojas; Sofía Irigoyen; Raúl Flores-Cartes (Universidad de Concepción., 2021)
Fluoridation has been shown to be an effective measure against caries in children. The present study evaluates the cost-benefit of the fluoridated water program for the reduction of dental caries in 12-year-old children in the Biobío Region, the only region in Chile that has not implemented this program. An economic cost-benefit evaluation was carried out, comparing two alternative interventions: non-fluoridated drinking water versus fluoridated drinking water. The prevalence of caries, direct and indirect costs of the treatments, the cost of implementing the programs and the benefits of both interventions were estimated. From this study it is concluded that the savings in oral health costs in 12-year-old children when using fluoridating drinking water in the Biobío region is significantly higher than the cost involved in implementing the water fluoridation program, resulting in total savings for the Chilean state of $129,861,645 (USD$ 152,833) as well as an estimated reduction of 15% in the history of caries in the study population.